Secondary Metabolites from the Marine Sponges of the Genus Petrosia: A Literature Review of 43 Years of Research - Yeon-Ju Lee; Yeonwoo Cho; Huynh Nguyen Khanh Tran (Marine Drugs, 2021)
Sponges are prolific sources of various natural products that have provided the chemical scaffolds for new drugs. The sponges of the genus Petrosia inhabit various regions and contain a variety of biologically active natural products such as polyacetylenes, sterols, meroterpenoids, and alkaloids. This review aims to provide a comprehensive summary of the chemical structures and biological activities of Petrosia metabolites covering a period of more than four decades (between 1978 and 2020). It is also described in this review that the major groups of metabolites from members of the genus Petrosia differed with latitude. The polyacetylenes were identified to be the most predominant metabolites in Petrosia sponges in temperate regions, while tropical Petrosia species were sources of a greater variety of metabolites, such as meroterpenoids, sterols, polyacetylenes, and alkaloids.